Implementasi Keterampilan Bahasa Dalam Meningkatkan Konsep Diri Anak Usia Dini - Annisa, Annisa Nurul Falaah (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2020)
Language skills are children's skills that are used to pronounce sounds to express and convey thoughts and feelings. Language skills are a means to improve self-concept in children. This study aims to determine: 1) efforts to improve self-concept in early childhood at RA Zakiyyatul Athfal and 2) implementation of language skills in improving self-concept in early childhood at RA Zakiyyatul Athfal. This research is qualitative research with a descriptive approach. The main subjects in this study were teachers, parents, and students of RA Zakiyyatul Athfal. Data were collected through observation and interviews. The validity of the data is done by using source triangulation. The results showed that: 1) Efforts were made to improve the self-concept of early childhood at RA Zakiyyatul Athfal by implementing the 5M strategy or creating fun, motivating classes, creating an atmosphere of humor, giving awards, and calling students to perform. 2) The implementation of language skills in improving the self-concept of early childhood at RA Zakiyyatul Athfal is done by way of storytelling, singing, and learning to pronounce words.